Brazil: what is to be done?. (1st August 2019) - Ferguson, Iain; Garcia, Maria Lucia
Abstract : The election of Jair Bolsonaro as President of Brazil on 28 October 2018 sent shock waves across the world. Bolsonaro is a retired army officer and Far Right politician who has made clear his admiration for the brutal military junta that ruled Brazil from 1964 to 1985. Iain Ferguson interviewed Brazilian social work academic Maria Lucia Garcia about the reasons for Bolsonaro's victory and what it will mean for Brazilian social work.